2003
DOI: 10.1080/0891693031000151247
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia Enterocolitica O:3 Isolated from Patients with or without Reactive Arthritis Induces Polyclonal Activation of B Cells and Autoantibody Production In Vivo

Abstract: The mechanisms by which arthritis-provoking pathogens such as Yersinia enterocolitica interact with the human immune system to produce inflammatory synovitis are not well known. One of the immunomodulating mechanisms used against these pathogens is the polyclonal activation of lymphocytes. In this study, we investigated the extent of the B-lymphocyte activation induced in mice by a strain of Y. enterocolitica O:3 (FCF 526) isolated from a patient with arthritis, and compared it with two other strains, a virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Polyclonal B cell activation (86,87) and parasite Fc-like receptors (88)(89)(90)(91) are thought to be partially responsible for anti-parasite ineffective humoral responses. In diverse infection models of strong polyclonal B cells responses, the most common isotypic distribution pattern is characterized by an increase in IgG2 subclasses (87,(92)(93)(94). Thus, polyclonal antibodies induction might constitute an evasion strategy exploited by E. granulosus to favour its survival.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal B cell activation (86,87) and parasite Fc-like receptors (88)(89)(90)(91) are thought to be partially responsible for anti-parasite ineffective humoral responses. In diverse infection models of strong polyclonal B cells responses, the most common isotypic distribution pattern is characterized by an increase in IgG2 subclasses (87,(92)(93)(94). Thus, polyclonal antibodies induction might constitute an evasion strategy exploited by E. granulosus to favour its survival.…”
Section: Discussionmentioning
confidence: 99%
“…Crespo et al [17] showed that lipopolysac- charides (LPS) are linked to anti-myelin, anti-actin or anti-laminin antibodies, and that Yersinia Outermembrane Proteins (Yops) are linked to antimyelin, anti-thyroglobulin or anti -cardiolipin antibodies. Silva et al discovered anti-myelin and anti-myosin antibodies in the sera of Yersinia enterocolitica O:3 infected mice [18]. This polyclonal activation in response to bacterial antigens creates many CICs able to be deposited in subcutaneous tissue and induce EN.…”
Section: Discussionmentioning
confidence: 99%
“…Os ativadores policlonais têm a capacidade de induzir a proliferação de múltiplos clones de linfócitos B, assim como aumentar a expressão de moléculas como classe II do MHC, CD69, CD25 e moléculas costimuladoras como CD80 e CD86 na superfície dos linfócitos B (Nashar et al, 1997;Montes et al, 2002). Os anticorpos produzidos durante a ativação policlonal reconhecem antígenos heterólogos e antígenos homólogos como actina, mioglobulina, miosina, tiroglobulina e DNA (Montes et al, 1996;Hunziker et al, 2003;Silva et al, 2003 (Gobet et al, 1988;Ochsenbein et al, 1999) e, no caso da IgM, participam da resposta imune inata ativando a via clássica do complemento.…”
Section: A Ativação Policlonal Dos Linfócitos B E a Produção De Anticunclassified